2017
DOI: 10.1080/17461391.2017.1411528
|View full text |Cite
|
Sign up to set email alerts
|

Transition phase clothing strategies and their effect on body temperature and 100‐m swimming performance

Abstract: Wearing warm clothing during a 30-min transition phase improved swimming performance by 0.6%, compared to limited clothing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 23 publications
0
29
1
5
Order By: Relevance
“…In half the studies (n = 7), it was concluded that swimmers performed significantly better after a regular warm-up than over a shorter or dryland warm-up [ 4 , 6 , 7 , 11 , 12 , 21 , 22 ]. However, a warm-up had a small effect on time trial performance across most studies [ 3 , 6 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In half the studies (n = 7), it was concluded that swimmers performed significantly better after a regular warm-up than over a shorter or dryland warm-up [ 4 , 6 , 7 , 11 , 12 , 21 , 22 ]. However, a warm-up had a small effect on time trial performance across most studies [ 3 , 6 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In half the studies (n = 7), it was concluded that swimmers performed significantly better after a regular warm-up than over a shorter or dryland warm-up [ 4 , 6 , 7 , 11 , 12 , 21 , 22 ]. However, a warm-up had a small effect on time trial performance across most studies [ 3 , 6 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 20 , 22 ]. This suggests there is some discontinuity among and within studies, but also suggests that there is a relationship between a warm-up and swimming performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T tym was recorded via tympanic measurements. MST was recorded at four sites of the body: Chest (C), Arm (D), Thigh (H) and Leg (J), as described in Galbraith & Willmott [ 25 ]. All temperature measurements were taken three times, with the mean values reported.…”
Section: Methodsmentioning
confidence: 99%